2021
DOI: 10.3389/fmolb.2021.602227
|View full text |Cite
|
Sign up to set email alerts
|

Risk Signature Related to Immunotherapy Reaction of Hepatocellular Carcinoma Based on the Immune-Related Genes Associated With CD8+ T Cell Infiltration

Abstract: Background: Hepatocellular carcinoma (HCC) is the most common histological type of liver cancer, with an unsatisfactory long-term survival rate. Despite immune checkpoint inhibitors for HCC have got glories in recent clinical trials, the relatively low response rate is still a thorny problem. Therefore, there is an urgent need to screen biomarkers of HCC to predict the prognosis and efficacy of immunotherapy.Methods: Gene expression profiles of HCC were retrieved from TCGA, GEO, and ICGC databases while the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For now, many HCC‐specific prognostic signatures have been constructed by bioinformatic analysis [ 26 , 27 ]. Although several prognostic models based on anoikis‐related genes for HCC have been established, signatures with anoikis‐related lncRNAs have not been identified [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…For now, many HCC‐specific prognostic signatures have been constructed by bioinformatic analysis [ 26 , 27 ]. Although several prognostic models based on anoikis‐related genes for HCC have been established, signatures with anoikis‐related lncRNAs have not been identified [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Now, several anti-PD-1 antibodies have been approved by the Food and Drug Administration (FDA) such as nivolumab which was permitted to treat patients with advanced HCC for the second-line approach, and pembrolizumab which was also favored to use in the patients diagnosed at advanced stages [ 9 , 10 ]. Moreover, a recent clinical trial targeting unresectable HCC composed of atezolizumab (anti-PD-L1) and bevacizumab (anti-VEGF) reported that increased overall survival (OS) and progression-free survival (PFS) were observed in the combined group than sorafenib alone group [ 11 ].…”
Section: Introductionmentioning
confidence: 99%